Spontaneous germ cell death by apoptosis in epididymis of the adult bat Artibeus lituratus - Taboga, S. R. [UNESP] (1999)
Many factors can lead cells to apoptosis during the various stages of cell life. This study was undertaken to characterize germ cell death in the epididymis of the adult Artibeus lituratus by histochemical and immunohistochemical techniques using light microscopy and transmission electron microscopy. The results showed that cells with a nuclear phenotype and ultrastructural characteristics of chromatin compaction were common in apoptosis. The Apoptag test confirmed that the suspected cells were apoptotic. It is suggested that immature germ cells, when released from the germinative epithelium, may be directed towards the epididymis instead of being disposed of in the testicle. Furthermore, intact immature cells can leave the testicle in the initial phases of apoptosis and complete this phenomenon in the epididymis.